Oxford University Research Archive (ORA): themed 'Collections’ - Partridge, J (Open Repositories Conference, 2024)
Many areas of research are undertaken at the University of Oxford. ORA Collections aim to bring content available in the repository, covering specific themes of research, together in to a single presentable and searchable space; showcasing all types of work (articles, conference papers, book sections, theses, data, etc.) together for engagement and reference. To avoid manual curation of content for an ORA Collection, SOLR queries have been used to present a work within a theme. This has involved development of SOLR join queries and targeted field indexing to refine search results to the relevance of a collection theme. Three collections have been launched so far, focusing on research themes of COVID-19, Climate, and Artificial Intelligence research. With the creation of each collection the mechanism for curating and presenting results have been developed and refined. The collections have been well received so far with the Climate Research Collection being shortlisted as a finalist in the Green Gown Awards in association with UKRI. We hope that the work done with ORA will provide inspiration to others in presenting themed research collections as well as being able to share the development with SOLR queries. Further reading at: https://ora.ox.ac.uk/objects/uuid:5c46148d-6739-4865-bae7-08fe7af87d24